The effect of detuned wavelength in the dynamic performance of distributed feedback lasers operating at O band and C band. Issue 4 (14th December 2019) - Cantú, Horacio I.; McKee, Andrew; Ivanov, Pavlo; Watson, Scott; Kelly, Anthony E.
Abstract: A comparison is presented between the experimental dynamic behavior of detuned AlInGaAs ridge waveguide distributed feedback lasers operating at O band and C band at two different temperatures. The nominal center wavelengths at 25°C for the set of devices studied were 1270, 1310, and 1550 nm. Preliminary static characterization of the samples showed consistent trends between wavelength detuning, characteristic temperature, and power output. For all set of samples, the characteristic temperature was substantially higher for the samples detuned to longer wavelengths (red) at room temperature. At the temperature of 85°C, a higher power efficiency was observed for those samples that thermally shifted nearer the peak optical gain. Resonance frequencies were extracted at 25°C and 85°C by means of electro‐optical transmission measurements and relative intensity noise measurements. The extracted values confirmed that at room temperature the samples detuned to shorter wavelengths (blue) showed the highest modulation efficiencies. At the temperature of 85°C, however, the wavelength and optical gain thermal shift makes those same samples to have the lowest resonant frequencies. The dynamic trends over temperature were clearer for the O band set of samples, while the detuning had a less pronounced effect at C band. The range of maximum resonance frequencies studied was from 12 to 14 GHz, which makes the devices suitable for uncooled communication applications at multi‐gigabit data rates.